Synthesis of 2,5-dibenzilidin cyclopentanone from benzaldehyde and cyclopentanone by solvent variation - Pudjono .; Supardjan .; Tri Irawati (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2006)
The 2,5-dibenzilidine cyclopentanone is a Pentagamavunon-0 analogues (PGV-0) that showed an antiproliferative activity on raji, myeloma and Hella cells. This compound can be synthesized by condensation reaction of a keton and an aldehide by using acid or base as catalyst. The synthesis was carried by reacting cyclopentanone (10 mmol), benzaldehide (20 mmol) and potassium hydroxide 30% (20 mmol) at 5oC, followed by neutralize the reaction product with hydrochloride acid and the compound was obtained by crystalization on CCl4. It showed that rendemen in organic solven: [methanol (96.3 %), ethanol (73.2 %) and isopropanol (67.7%)]. The purity of the product was determined by using melting point and TLC methods . Structural elucidation was carried out by spectroscopic method ( UV-VIS, IR, H1-NMR and MS spectra). It could be concluded that the compound is 2,5-dibenzilidincyclopentanone.Key words: 2,5-dibenzilidincyclopentanone, catalyst, solven.